Graph theory reveals dysconnected hubs in 22q11DS and altered nodal efficiency in patients with hallucinations - Ottet, Marie-Christine; Schaer, Marie; Debbané, Martin; Cammoun, Leila; Thiran, Jean-Philippe; Eliez, Stephan (Frontiers in Human Neuroscience, 2013)
Schizophrenia is postulated to be the prototypical dysconnection disorder, in which hallucinations are the core symptom. Due to high heterogeneity in methodology across studies and the clinical phenotype, it remains unclear whether the structural brain dysconnection is global or focal and if clinical symptoms result from this dysconnection. In the present work, we attempt to clarify this issue by studying a population considered as a homogeneous genetic sub-type of schizophrenia, namely the 22q11.2 deletion syndrome (22q11.2DS). Cerebral MRIs were acquired for 46 patients and 48 age and gender matched controls (aged 6 to 26, respectively mean age = 15.20 ± 4.53 and 15.28 ± 4.35 years old). Using the Connectome mapper pipeline (connectomics.org) that combines structural and diffusion MRI, we created a whole brain network for each individual. The graph theory was used to quantify the global and local properties in the brain network organization for each participant. A global degree loss of 6% was found in patients’ network along with an increased Characteristic Path Length. After identifying and comparing hubs, a significant loss of degree in patients’ hubs was found in 58% of them. Based on Allen’s brain network model for hallucinations, we explored the association between local efficiency and symptom severity. Negative correlations were found in the Broca’s area (p<0.004), the Wernicke area (p<0.023) and a positive correlation was found in the dorsolateral prefrontal cortex (DLPFC) (p<0.014). In line with the dysconnection findings in schizophrenia, our results provide preliminary evidence for a targeted alteration in the brain network hubs’organisation in individuals with a genetic risk for schizophrenia. The study of specific disorganization in language, speech and thought regulation networks sharing similar network properties may help to understand their role in the hallucination mechanism.